Police in India : problems and perspectives - Mathur, Krishna Mohan (New Delhi, 1991)
The book examines how the police developed in various societies, what role it is expected to play in a pluralistic developing society and many such critical issues which provide proper perspectives to the police.
Keywords: Police - India